Studi Perbandingan Pengenalan Karakter Aksara Lampung Dengan Metode Deteksi Tepi Roberts dan Sobel - Halim Abdillah Sholeh; Yessi Mulyani; Hery Dian Saptama (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
The culture of Lampung script is now rarely used and will get extinct. In order to preserve the culture, this digital research about Lampung script with image processing method and pattern recognition is conducted. This research is divided into two stages, training and testing. Training stage conducted image processing and training the artificial neural network (ANN) backpropagation. One past of image processing is edge detection. The edge detection method is used to analyze the Lampung script character to find the line pattern of the letters. The image processing methods used in image edge detection are Roberts edge detection method and Sobel edge detection method. The result of image processing will get into testing stage. Sobel method has better performance on recognizing. Lampung script character, in which the result from testing Lampung script character gives 28.5 % of error for Roberts detection method and 14.5 % of error for Sobel detection method.